Clinical Impact of Prophylactic Antibiotic Treatment for Self-Expandable Metallic Stent Insertion in Patients with Malignant Colorectal Obstruction - Jong-Sun Kim; Wan-Sik Lee; Cho-Yun Chung; Hyung-Chul Park; Dae-Seong Myung; Chan-Young Oak; Mi-Young Kim; Mi-Ok Jang; Seung-Ji Kang; Hee-Chang Jang; Sung-Bum Cho; Hyun-Soo Kim; et al. (Gastroenterology Research and Practice)
Purpose. The aim of this study was to determine the efficacy of prophylactic antibiotics (PA) for reducing the infectious complications and the potential risk factors responsible for the infectious complications after stent insertion for malignant colorectal obstruction. Methods. We performed a retrospective review of 224 patients who underwent self-expandable metallic stent (SEMS) insertion for malignant colorectal obstruction from May 2004 to December 2012. Results. There were 145 patients in the PA group and 79 in non-PA group. The CRP level in PA group was significantly higher than that in non-PA. Abdominal tenderness and mechanical ileus were significantly more frequent in PA group than those in non-PA. The frequency of post-SEMS insertion fever, systemic inflammatory response syndrome (SIRS), and bacteremia was not significantly different between PA and non-PA groups. In multivariate analysis, the CRP level was risk factor related to post-SEMS insertion SIRS. However, in propensity score matching analysis, there was no independent risk factor related to post-SEMS insertion fever, SIRS, and bacteremia. Conclusion. The use of PA in patients with malignant colorectal obstruction may be not effective to prevent the development of infectious complications after SEMS insertion.